Challenges of Indonesian Islamic Civilization in the Digital Era - Lina Pusvisasari; Natasya Ramadina Azura; Muhammad Gani Mulya P (al-Wadhih: Journal of Islamic History and Civilization, 2025)
Islam encompasses principles and values in various aspects of life that guide man. However, in its current development, the value order of Islamic civilization has begun to erode, including in Indonesia. This is caused by various factors, one of which is developments in the digital era. The development of digital technology has had a significant impact on Islamic civilization in Indonesia. The digital age has presented complex challenges in maintaining and strengthening the role of Islam in society. The problem that many Muslims experience today is the ease of adopting Western (cultural) habits that are not in accordance with their beliefs. In this discussion, the aim is to provide a description of the challenges in the digital era, especially the internet, to Islamic civilization in Indonesia and to offer alternatives on how technology can be used to strengthen Islamic civilization. Technology can have a positive impact on the Islamic community in Indonesia if it relies on Islamic principles.